HUBUNGAN PENGETAHUAN DAN SIKAP IBU TERHADAP KUNJUNGAN IBU BALITA DI KELOMPOK BINA KELUARGA BALITA (BKB) MELATI INDAH DESA TOAPAYA SELATAN KECAMATAN TOAPAYA KABUPATEN BINTAN PROVINSI KEPULAUAN RIAU - Elinda, Elinda; Yunifitri, Astri; Suryanti, Suryanti (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2020)
Malnutrition problem is the main focus of the President of Indonesia. In this case President Joko Widodo and World Bank President Jim Yong Kim discussed the stunting problem or malnutrition which reached number of children in the country. Malnutrition in the Riau Islands Province in 2017 was a parental problem (63.4%). One of a series of sustained and guided activities to ensure optimal growth and development of infants rolled out by the government is the "TODDLER’S FAMILY DEVELOPMENT" Program. The Ministry of Health reported that around 150.8 million toddlers in the world experienced stunting and 17.7% of children in Indonesia experienced malnutrition. Several factors that affect the sustainability of the toddler’s family development program among which is influenced by toddler’s families. Lack of sufficient level of education in caring for and educating children can affect the development of toddlers. The purpose of this study is to determine whether there is a relationship between knowledge and attitudes of mothers towards the visit of mothers in the Toddler Family Development Group. This study adopted an analytical survey research design using the Cross Sectional approach carried out in the South Toapaya Village of Toapaya subdistrict in March-August 2019. The population and sample were 31 mothers with a total sampling technique. From the data analysis using chi square, the results of 31 mothers of toddlers were mostly obtained good knowledge (71%), good attitude (71%) and irregular visits of mothers to the Toddler Family Development Group (68%). Statistical test results have a relationship between knowledge where p = 0.001 <0.05, and attitude p = 0.001 <0.05. In conclusion, there is a significant relationship between knowledge and attitude with the visit of a mother with toddler in South Toapaya Village, Toapaya District. It is suggested that the Toddler Family Development Program is able to support cadres to develop and form a Toddler’s Family Development Group in other villages